New families of star-supermagic graphs - Anak Agung Gede Ngurah (Indonesian Journal of Combinatorics, 2020)
A simple graph G admits a K1,n-covering if every edge in E(G) belongs to a subgraph of G isomorphic to K1,n. The graph G is K1,n-supermagic if there exists  a bijection f : V(G) ∪ E(G) → {1, 2, 3,..., |V(G) ∪ E(G)|} such that for every subgraph H' of G isomorphic to K1,n,  ∑v ∈ V(H')  f(v) + ∑e ∈ E(H') f(e) is  a constant and f(V(G)) = {1, 2, 3,..., |V(G)|}. In such a case, f is called a K1,n-supermagic labeling of G.  In this paper, we give a method how to construct K1,n-supermagic graphs from the old ones.